Internal Control that Influences Performance Efficiency of Financial, Accounting and Auditing Department of Local Administrative Organization, Songkhla Province: Perspective of the Division Director of Division Finance - Garee, Alif; Buasri, Chanticha; Rungruang, Prasit (Arts of Management Journal, 2024)
This article aimed to study internal controls that influence the performance efficiency of a local administrative organization's finance, accounting, and auditing departments in Songkhla province from the perspective of the Division Director of Division Finance. This research was quantitative, using a questionnaire as a tool to collect data from a sample group. The division director of the division finance local administrative organization, Songkhla Province was the main information provider and received 59 responses. Statistics including percentage, mean, standard deviation, and multiple regression analysis, were used to test hypotheses. The results showed that internal control, control environment, risk assessment, and information and communication had a positive influence on the performance efficiency of the finance, accounting, and auditing departments of the Local Administrative Organization, Songkhla Province with a statistical significance of 0.05. The control activities had a negative influence on the performance efficiency of the finance, accounting, and auditing departments of the Local Administrative Organization, Songkhla province statistical significance of 0.05. Monitoring and evaluating the performance efficiency of the finance, accounting, and auditing departments of the Local Administrative Organization, Songkhla Province was not a statistical implication.